Tinjauan Pengaruh Kualitas Genteng Beton Dengan Bahan Tambah Serat Kaca - Setiyadi, Deni Wahyu, Ir. Ali Asroni,M.T, Budi Setiawan,S.T.,M.T (2016)
The rapid development of current occupancy, it is necessary that the roof covering materials must meet the requirements determined by the SNI 0096-2007. Is one of the concrete tile roof coverings are good and strong, but has a wide range of weakness, which is expensive and fairly heavy, so it requires a strong roof truss structure. This study aimed to determine the effect of large glass fibers to bending loads, the nature seemed, water seepage, water absorption, the absorption of heat and uniformity of size. The proportion of the mixed materials are 1 Portland Cement: 2 Limstone Mill : 2.5 Sand and the percentage of fiberglass addition is 0%; 1%; 1.5%; 2%; 2.5% of the weight of the sand. The tests is carried out in accordance with the requirements of SNI 0096-2007. The results of the look characteristic are the concrete tile has smooth surface, has right angle, there are no cracks or other defects. Meanwhile, the result of the size uniformity testing shows the average concrete tile is P = 420 mm, L = 335 mm, thickness of flat section = 14.02 mm, thickness of overlap section = 8.5 mm, length of hook = 420 mm, width of hook = 12.5 mm, high of hook = 15.42 mm, width of overlap section = 78 mm, depth of slot = 34.5 mm. The average percentage result of the heat absorption testing is 0% = 86.07%; 1% = 86.44%; 1.5% = 85.06%; 2% = 86.01%; 2.5% = 84.83%. Meanwhile, the average percentage result of water absorption testing is 0% = 9.06%; 1% = 9.73%; 1.5% = 8.22%; 2% = 8.77%; 2.5% = 10.73%. Then, the average percentage result of water seepage concrete tile is 0%; 1%; 1.5%; 2%; 2.5% and there is no seepage. While the average percentage result of the bending load characteristic testing of the augmentation of fiberglass is 0% = 977.58 N; 1% = 1130.10 N; 1.5% = 1138.74%; 2% = 1148.47 N; 2.5% = 1186.22 N. according to the test results, it can be concluded that the highest average of bending load value is obtained from 1.5% of fiberglass, it is equal to 148.89 kg. The result of concrete tile augmented with fiberglass has met the SNI 0096-2007 in terms of characteristic of look, water seepage, and uniformity of size. Meanwhile, in terms of heat absorption, water absorption and some bending load characteristics has not meet the requirement.